Project-Based Knowledge in Organizing Open Innovation - Bonesso, Sara; Comacchio, Anna; Pizzi, Claudio (Springer London : Imprint: Springer, 2014)
Enriching understanding of the current theoretical debate on project-based open innovation, 'Project-based Knowledge in Organizing Open Innovation' draws on innovation management literature and knowledge-based perspectives to investigate the relationship between knowledge development at project level and the strategic organization of open innovation. Addressing the still open issue of how the firm level should be complemented by studies at the project level of analysis, this book provides theoretical and empirical arguments on the advantages of a more fine-grained level of analysis to understand how firms organize their innovation processes across boundaries. The book also addresses the emerging interest in the management literature on project-based organizations, and on the relevance of project forms of organizing in a knowledge-based economy. Through field research in different industrial settings , this book provides empirical evidence on how firms design open innovation project-by-project and it will appeal to scholars and students in business and management, in particular those in innovation management, organization theory, and strategic management.